The Relationship Among Safety Management System, Safety Climate And Safety Performance In Construction Sites - Leong, Kit Keng (2010)
There is a lack of conceptual model seek about the relationship among safety management system, safety climate and safety performance. Safety climate is linked to safety performance and more research or model is needed to validate the relationship (Choudhry et al., 2008). Unless identified which factors have the greatest impact on health and safety, if not the safety management system compliance auditing will have little impact on organization’s overall safety performance (Makin and Winder, 2008). Thus, a self-administered questionnaire by using 7 points scale that includes the safety management system, safety climate, and safety performance scales were used to collect the data in construction sites of Malaysia.